PENGEMBANGAN E-COMIC SEBAGAI MEDIA PEMBELAJARAN EKONOMI KELAS X DI SMAN 7 MALANG POKOK BAHASAN SISTEM PEMBAYARAN DAN ALAT PEMBAYARAN - Irawati *; Lisa Rokhmani (Universitas Negeri Malang, 2016)
Based on interview and observation carried out by the researcher to the Economy teacher in SMAN 7 Malang, the teachers find it difficult to deliver Economic material by adding information related with the environment around students in both the social environment and the natural environment in the process of teaching and learning in the classroom. Teachers only use verbal means namely lecture method. Based on the problems faced by the teachers, researchers provide a solution using instructional media in the form of e-comic highlighted to the payment system by adding information that enhances the students awareness of the surrounding. This type of research is developmental research by using descriptive qualitative analysis with using a model research and development Borg and Gall. The study was conducted in 10th Grade of Social Science of 4 in SMAN 7 Malang. The instrument of this study uses a questionnaire derived from the expert validation for media, experts for the material and the assessment from students to the media. Based on the result of the questionnaire, the developmental media used e-comic as an instructional media highlighted on payment systems and payment instruments subject, has a decent criteria with the acquisition of a percentage around 98% from the expert for material, 95% for instructional media experts and 97% from the questionnaire assessment of students that can be used to assist the teachers in the teaching and learning process in the classroom. It is suggested for the teacher to provide reinforcement at each learning activity using e-comic media as development results. Keywords: Instructional Media, Electronic, Technology, e-comic